Analysis of health communication research topics based on term clustering - Tapia, Elsa Carmen Oscuvilca; Sánchez, Fredy Ruperto Bermejo; Choque, Efraín Ademar Estrada; Ayudante, William Rogelio Peña; Lucho, Miriam Milagros Noreña (Iberoamerican Journal of Science Measurement and Communication (Online), 2025)
Objective. This study employed term clustering to analyze health communication research topics and to identify thematic groupings, scholarly impact, and term interconnectivity. Methods. A systematic analysis was conducted using a Scopus dataset comprising terms related to health communication research, accompanied by spatial coordinates, cluster assignments, and impact metrics such as link strength, occurrences, and average citations. The methodology was structured in a way that enabled the presentation of four comprehensive analyses. The following four analyses were conducted: 1) topic cluster analysis to identify and label thematic groupings; 2) impact analysis to evaluate the scholarly influence of different terms using citation metrics; and 3) term connectivity analysis to visualize the network of relationships between terms. The data were processed in several steps, including cleaning and structuring the dataset, interpreting the clusters thematically, and creating a network graph using NetworkX and Matplotlib. Results. The topic cluster analysis yielded seven discrete research clusters, each representing a primary area of focus. These included the following areas: adolescent and youth health, behavioral interventions, advocacy and policy, global health, prevention, mental health, and digital communication. The impact analysis evidenced the scholarly significance of key terms such as "behavior change," "advocacy," and "mental health," with robust citation metrics indicating their influence within the field. The connectivity analysis demonstrated a highly interconnected research landscape, with central nodes linking multiple thematic areas, emphasizing the field's multidisciplinary nature. Conclusions. The field of health communication research is distinguished by a dynamic and evolving panorama that integrates behavioral science, policy influence, cultural competence, and modern technology. The study demonstrates that effective health communication strategies are inherently interdisciplinary, drawing on diverse insights to address a broad spectrum of public health challenges. The findings indicate that future research should continue to capitalize on these interrelated themes, emphasizing comprehensive and responsive communication strategies to address evolving societal needs and achieve meaningful health outcomes.